Salvianic acid A promotes osteogenic differentiation of bone marrow mesenchymal stem cells in senile osteoporosis through bromodomain-containing protein 4/Ariadne RBR E3 ubiquitin-protein ligase 1/Rubicon axis - Zhixian Xu; Jun Luo; Yongfa Zhang; Zhenyu Zhang; Jie Xu (Journal of Traditional and Complementary Medicine)
Background: Senile osteoporosis (SOP) seriously disturbs the life of elder people. Inhibition of autophagy can contribute to the progression of SOP. Meanwhile, Salvianic acid A (SA) could inhibit the progression of SOP, and it could regulate the autophagy. However, the relationship between SA and autophagy in SOP remains to be further explored. Methods: Bone marrow mesenchymal stem cells (BMSCs) were isolated from senescence-accelerated mouse propensity 6 (SAMP6) mice. Then, Alizarin red S (ARS) and alkaline phosphatase (ALP) staining were performed to analyze the osteogenesis in BMSCs. Meanwhile, protein levels were investigated using Western blot. The binding between Ariadne RBR E3 ubiquitin-protein ligase 1 (ARIH1) and Rubicon was investigated using Co-IP. ChIP and Dual-luciferase assay were used to explore the binding between bromodomain-containing protein 4 (BRD4) and ARIH1 promoter region. Results: The levels of BRD4, Rubicon and p62 were upregulated in BMSCs from SAMP6 mice, while ARIH1, Beclin1, ATG5 and the ratio of LC3II/LC3I were downregulated. SA could promote the osteogenesis of BMSCs through mediating the autophagy. In addition, SA dose-dependently upregulated the levels of OPN, OCN and Runx2 in BMSCs from SAMP6 mice. ARIH1 could degrade Rubicon through ubiquitination, and BRD4 could transcriptionally inhibit the expression of ARIH1. Meanwhile, SA obviously promoted the autophagy and osteogenesis in BMSCs through mediation of BRD4/ARIH1/Rubicon axis. Conclusion: SA promoted osteogenic differentiation of BMSCs in senile osteoporosis through BRD4/ARIH1/Rubicon axis. Thus, our study might provide a new theoretical basis for developing the new strategies against SOP in clinic.